ANALISIS KESULITAN SISWA SMP DALAM MENGERJAKAN SOAL MATERI STATISTIKA - Alivia Salsabila Maharani; Siti Chotimah; Eka Senjayawati (IKIP Siliwangi, 2022)
This containt of research is conducted and aimed at knowing and analyzing how difficult students experience in working on problems in class VIII statistical material. This research using a descriptive qualitative research method with learning process through a contextual approach. In this study, the subjects studied were 10 class VIII junior high students, consisting of 4 male students and 6 female students. This study used instrument test of 5 points every question of description, questions that are sequenced based on the cognitive level of bloom taxonomy. Techniques and data analysis are used by analyzing data such as data reduction, presentation of data and inferring results in research. The tests are then processed by percentage measuring results on every indicator with difficulty level ranging from it category is too easy, easy, to be enough, difficult, and very difficult. Based on the results of the overall difficulty level research falls into the difficult category with a percentage result of 52%, on the problem with indicators making conclusions, making decisions from the data and designing data from the distribution given with a percentage result of 80% which belongs to the category is very difficult.